Short- and long-term results of an inpatient programme to manage Complex Regional Pain Syndrome in children and adolescents. Issue 2 (May 2017) - Cucchiaro, Giovanni; Craig, Kevin; Marks, Kerri; Cooley, Kristin; Cox, Thalitha Kay Black; Schwartz, Jennifer
The aim of this retrospective study was to determine whether an inpatient approach and the use of regional anaesthesia techniques can accelerate the recovery to normal functions in children with Complex Regional Pain Syndrome (CRPS). This study looked at the data of patients admitted to the rehabilitation unit with a diagnosis of CRPS from January 2010 to April 2015. Variables such as hospital stay, medications administered, regional anaesthesia procedures, changes in functional status prior to treatment and at the time of discharge, psychological evaluation and diagnosis were evaluated. A total of 31 patients (21 females and 10 males) were admitted with a diagnosis of CRPS 1 and 2. In all, 97% of the patients received a peripheral or central nerve catheter for an average of 4 days with pain scores of Verbal Numeric Scale (VNS) score = 1.0 ± 0.7 and an average length of hospital stay of 8.2 ± 2.6 days. The modified Functional Independence Measure for Children (WeeFIM) scores and Canadian Association of Occupational Therapists tests significantly improved at the time of hospital discharge, as well as their pain scores, which decreased from 8.2 ± 2 to 1.6 ± 3. In conclusion, these data suggest that the use of regional anaesthesia techniques and an intensive inpatient rehabilitation programme could accelerate the recovery of children with CRPS.